2018
DOI: 10.1007/s42452-018-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of brake pad developed from coconut shell reinforcement material using central composite design

Abstract: In this work, locally sourced non-hazardous materials were used to produce brake pad using grey relational analysis (GRA) and experimental design via central composite design. Raw materials selected for production include coconut shell, epoxy resin (binder), graphite (friction modifier) and aluminum oxide (abrasive). Twenty-seven samples were produced separately using coconut shell as reinforcement material by varying process parameters. Formulation of the brake pads samples was done using rule of mixture and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 17 publications
0
30
1
Order By: Relevance
“…In addition, curing time has the greatest impact on the coconut shell-reinforced friction material’s ultimate tensile strength and hardness, accounting for 31.40% and 30.38% accordingly. In contrast, heat treatment time has the greatest impact on the coconut shell-reinforced brake pad’s friction coefficient and wear rate, accounting for 24.23% and 46%, accordingly [ 34 ].…”
Section: Factors Affecting the Performance Of Brake Padmentioning
confidence: 99%
“…In addition, curing time has the greatest impact on the coconut shell-reinforced friction material’s ultimate tensile strength and hardness, accounting for 31.40% and 30.38% accordingly. In contrast, heat treatment time has the greatest impact on the coconut shell-reinforced brake pad’s friction coefficient and wear rate, accounting for 24.23% and 46%, accordingly [ 34 ].…”
Section: Factors Affecting the Performance Of Brake Padmentioning
confidence: 99%
“…The study concluded that CS is an effective substitute for asbestos in producing brake pads. Abutu et al [24] developed CS reinforced automotive brake pads using the gray relational analysis and the central composite experimental design approach. The developed samples produced less noise and vibration during application when compared to the control sample.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, CCD via RSM experimental design consisting of moulding pressure (MP), moulding temperature (MT), curing time (CT) and heat treatment (HTT) was built in accordance to standard L27(2) 4 using Minitab 17 statistical software. The factor levels of process parameters and experimental design matrix are shown in Table 1 and Askeland (1985) utilising density ( ) as a criteria while production was carried out on a compression moulding machine situated at Federal College of Chemical and Leather Technology (FCCLT), Samaru, Zaria (Polymer workshop) and was conducted using the procedure adopted by Abutu et al (2019) which involved utilising varying process parameters shown in Table 2 with constant percentage composition as obtained from ROM. This procedure further involved pouring and mixing epoxy resin and hardener (catalyst) in the ratio of 2:1 in a separate container, followed by filling of mould cavity with total mixture of mixed binder and filler materials, then, the withdrawal of cured samples from the moulding machine, cooling of samples and removal of the cooled samples from the mould.…”
Section: Design Of Experiments Using Rsm Design Techniquementioning
confidence: 99%